Group Dynamics and Cronyism in Village Development Planning Participation - Zulmasyhur, Zulmasyhur; Avianto, Bhakti Nur (Universitas Malikussaleh, 2019)
Musrenbangdes consist of formation activities, methods, programs and social movements with the aim of accommodating and identifying problems and needs that exist in each hamlet, Musrenbangdes conducted to filter aspirations and formulate policy directions. So there is a contribution to the role of village deliberation decision making that can increase community participation in rural infrastructure development. However, good planning is not optimal because it can be seen from the weakness of the ability of government officials, the community in implementing Musrenbangdes still has shortcomings, both seen technically and its performance is also not optimal, does not follow the procedures set by the Musrenbangdes stages so that the results obtained are not effective, efficient , not optimal and not in accordance with community needs. Factors hampering the Musrenbangdes, namely: weak capacity of village government in making development planning, cronyism of government and capacity building are weak and institutions that handle Musrenbangdes, weaknesses in identifying problems, and weak government data and information support. Influential actors in the process of preparing village development plans, among others, lack of planning workforce resources, limited time, development planning that is not integrated and the allocation of projects is ineffective and not based on priority scale.